2017
DOI: 10.1021/acscatal.7b01246
|View full text |Cite
|
Sign up to set email alerts
|

Ceria Catalysts at Nanoscale: How Do Crystal Shapes Shape Catalysis?

Abstract: Engineering the shape and size of catalyst particles and the interface between different components of heterogeneous catalysts at nanometer level can radically alter their performances. This is particularly true with CeO2-based catalysts, where the precise control of surface atomic arrangements can modify the reactivity of Ce 4+ /Ce 3+ ions, changing the oxygen release/uptake characteristics of ceria, which, in turn, strongly affects catalytic performance in several reactions like CO, soot and VOC oxidation, W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

19
487
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 610 publications
(510 citation statements)
references
References 190 publications
(517 reference statements)
19
487
0
4
Order By: Relevance
“…61 Furthermore, oxygen vacancies have been found to play a highly important role in oxidation reactions over ceria and metal NPs supported on ceria. 37 For example, in the oxidation of toluene oxygen vacancies contribute to the activation of the substrate via surface oxygen vacancies, and the migration of bulk oxygen to the surface. 53 The concentration of Ce 3+ has also been correlated with the adsorption of molecular oxygen by ceria and formation of superoxide species on the surfaces of ceria, and has been linked to the observed high catalytic oxidation activity of ceria in some oxidation reactions.…”
Section: Catalytic Activity Measurementmentioning
confidence: 99%
See 2 more Smart Citations
“…61 Furthermore, oxygen vacancies have been found to play a highly important role in oxidation reactions over ceria and metal NPs supported on ceria. 37 For example, in the oxidation of toluene oxygen vacancies contribute to the activation of the substrate via surface oxygen vacancies, and the migration of bulk oxygen to the surface. 53 The concentration of Ce 3+ has also been correlated with the adsorption of molecular oxygen by ceria and formation of superoxide species on the surfaces of ceria, and has been linked to the observed high catalytic oxidation activity of ceria in some oxidation reactions.…”
Section: Catalytic Activity Measurementmentioning
confidence: 99%
“…It is generally observed that ceria nanorods grow along the [100] direction with exposed {100} and {110} surfaces 28,37 although recent literature suggests that the {110} surfaces of ceria nanorods can reconstruct exposing large fractions of {111} nanofacets on the {110} planes. 38 The presence of defects and imperfections in the lattices of ceria nanorods is a consequence of the different plane exposures, 37 and play a vital role in the stabilization of metal NPs, which grow preferentially on surface defects sites where the contact area with the support is maximised.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is not an easy task to provide an explanation for the observed behavior of mixed Mn x Ce 1−x oxides compared to pure CeO 2 or MnO x . Trovarelli and Llorca have stressed the importance of size, shape, and degree of exposure of specific facets of ceria-based particles on their catalytic performance [30]. The distribution of specific nanofacets of ceria depends on its size and shape and leads to different reactivity in CO adsorption, for example [31].…”
Section: Discussionmentioning
confidence: 99%
“…By combining advanced acquisition and processing techniques, timeresolved HRTEM will enable new insights into the structural evolution of nanoparticle surfaces. In this work, we use time-resolved HRTEM to achieve high spatial and temporal resolution of surface atom migration on CeO2 nanoparticles, a material that is used extensively in catalysis applications due to its oxygen exchange properties [4].An aberration-corrected FEI Titan ETEM equipped with a Gatan K2 IS direct detection camera (with high detection quantum efficiency) was used to image CeO2 nanoparticles at 400 frames/second and 10 4 e -/(Å 2 s) in vacuum. A single frame of 1/400 second exposure is shown in Figure 1a), and due to the fast acquisition rate, the signal-to-noise ratio of the image was low.…”
mentioning
confidence: 99%